Transcranial Direct Current Stimulation to Enhance Cognitive Impairment in Parkinson's Disease: A Systematic Review and Meta-Analysis - Suarez-García, Diana M. A.; Grisales-Cárdenas, Johan S.; Zimerman, Máximo; Cardona, Juan F. (Frontiers in Neurology, 2020)
Cognitive deficits are increasingly being recognized in Parkinson's disease (PD). Recently, tDCS has been shown to exert positive effects as an adjunctive therapy on motor and nonmotor symptoms in PD. This systematic review and meta-analysis aim to provide an overview of reported evidence on the efficacy of tDCS interventions in the treatment of cognitive impairments in PD. A systematic literature review was conducted to examine articles that were published in the past ten years and that study the effects of tDCS on cognitive deficits in PD. PubMed, Scopus, and Scielo were searched. Eight tDCS studies involving 168 participants were included for the analysis. Meta-analysis results showed that anodal tDCS (atDCS) had various levels of effectiveness. In the pre-post stimulation analysis, a strong effect was reported for executive functions (pre-post: g = 1.51, Z = 2.41, p = 0.016); a medium effect was reported for visuospatial skills (pre-post: g = 0.27, Z = 0.69, p = 0.490); and weak effects were reported for attention (pre-post: g = 0.02, Z = 0.08, p = 0.934), memory (pre-post: g = 0.01, Z = 0.03, p = 0.972) and language (pre-post: g = 0.07, Z = 0.21, p = 0.832). However, in the pre-follow-up stimulation analysis, the duration of the effect was not clear. This study highlights the potential effectiveness of atDCS to improve cognition in PD patients but failed to establish a cause-effect relationship between tDCS intervention and cognitive improvement in PD. Future directions and recommendations for methodological improvements are outlined.